TINJAUAN YURIDIS TERHADAP PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DALAM TRANSAKSI JUAL BELI TANAH DAN BANGUNAN DI KOTA TANJUNG BALAI - CHAIRUMI CHAIRUMI (PREMISE LAW JURNAL, 2014)
ABSTRACT The collecting of BPHTB at Tanjung Balai is based on the Regional Regulation No. 2/2011 and the implementation of the system and procedure of collecting BPHTB, based on Perwal (Mayor’s Decree) No. 11/2011.The objective of the research was to find out how the system of collecting BPHTB in the transaction buying and selling land and/or buildings at Tanjung Balai, to find out legal certainty of the transaction of buying and selling land and buildings at Tanjung Balai related to the verification of DPPKA (Revenues Office of Regional Finance and Assets Management), and to find out the types of obstacle in collecting BPHTB at Tanjung Balai.The research was descriptive with judicial normative approach. The result of the research showed that the implementation of collecting BPHTB at Tanjung Balai, based on Perwal No. 11/2011, was not implemented according to the prevailing procedures since the research procedure of SSPD (Regional Tax Return Letter) of BPHTB and the payment procedure of BPHTB were not in accordance with the prevailing rules so that legal certainty for those who did the transaction was delayed. Keywords: Collecting BPHTB, Transaction of Buying and Selling, Land and Buildings